2018
DOI: 10.31235/osf.io/eah4w
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Does Children's Education Improve Parental Health and Longevity? Causal Evidence from Great Britain

Abstract: Parents with better-educated children are healthier and live longer, but whether there is a causal effect of children’s education on their parents’ health and longevity is still unclear. Previous research has been largely associational and was thus not able to account for all circumstances that confound children’s education and parental longevity. First, we demonstrate an association between adults' offspring education and parental mortality in the 1958 British birth cohort study, which remains substantial - a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…More recently, a handful of quasi-experimental studies have identified causal effects of children's education on parental health. In high-income settings, such as Sweden, additional children's education has generally led to modest and heterogeneous protective effects on parental mortality (Lundborg and Majlesi 2018;Potente et al 2018). In contrast, in low-resource settings, substantial benefits of children's education have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a handful of quasi-experimental studies have identified causal effects of children's education on parental health. In high-income settings, such as Sweden, additional children's education has generally led to modest and heterogeneous protective effects on parental mortality (Lundborg and Majlesi 2018;Potente et al 2018). In contrast, in low-resource settings, substantial benefits of children's education have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Parents of better-educated children are healthier and live longer. This association has been observed across high-income such as the United States, Finland, Taiwan and the United Kingdom, as well as in low and middle income countries, including China (Elo et al, 2018;Friedman and Mare, 2014;Lee et al, 2017;Potente et al, 2022). The reasons behind this association are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Lundborg and Majlesi (2018) exploit an educational reform in Sweden and find no effect of education on parental longevity across the board, however for fathers, having better-educated daughters is beneficial, particularly if fathers come from poorer backgrounds. Potente et al (2022) use linked census data to analyze the 1972 educational reform in England. They do not find an effect of eligibility to the reform on mothers or fathers, neither for self-reports of health nor for mortality.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations